A full‐scale thermophilic biofilter in the treatment of sludge drying exhaust: performance, microbial characteristics and bioaerosol emission. Issue 8 (2nd March 2018) - Yang, Kaixiong; Li, Lin; Ding, Wenjie; Liu, Junxin; Xue, Song
Abstract: BACKGROUND: Volatile organic compounds (VOCs), NH3, and SO2 generated from a sludge drying process were treated by a full‐scale thermophilic biofilter (FTB). The correlation between gaseous pollutants removal and the microbial community structure in the FTB was studied. Bioaerosols emission from the FTB was also investigated. RESULTS: More than 90% of VOCs, NH3, and SO2 were removed at steady state. The maximum elimination capacities of VOCs, NH3, and SO2 were 3.01, 1.83, and 5.13 g m ‐3 h ‐1, respectively. Analysis of clone libraries indicated that the structure of the bacterial communities showed temporal variation. Species that have the abilities of desulfuring and denitrifying, e.g. Alcaligenes sp., Comamonas sp., Sphingobacterium sp., and Bacillus sp., were abundant in the FTB. High bioaerosols concentration of nearly 2.3 × 10 3 CFU m ‐3 was detected in the FTB outlet. Most of the bacteria in bioaerosols were assigned to Pseudomonas sp., which were the main bacteria attached to the surface of packing materials. CONCLUSION: The FTB was highly efficient and showed potential for the removal of real complex gases at high temperature. The composition of the inlet stream influenced the species and abundance of microorganisms in the FTB. Control of bioaerosols emission should be taken into account in the future. © 2018 Society of Chemical Industry